Coordinated patterning of zebrafish caudal fin symmetry by a central and two peripheral organizers. Issue 8 (22nd April 2022) - Desvignes, Thomas; Robbins, Amy E.; Carey, Andrew Z.; Bailon‐Zambrano, Raisa; Nichols, James T.; Postlethwait, John H.; Stankunas, Kryn
Abstract: Background: Caudal fin symmetry characterizes teleosts and likely contributes to their evolutionary success. However, the coordinated development and patterning of skeletal elements establishing external symmetry remains incompletely understood. We explore the spatiotemporal emergence of caudal skeletal elements in zebrafish to consider evolutionary and developmental origins of caudal fin symmetry. Results: Transgenic reporters and skeletal staining reveal that the hypural diastema‐defining gap between hypurals 2 and 3 forms early and separates progenitors of two plates of connective tissue. Two sets of central principal rays (CPRs) synchronously, sequentially, and symmetrically emerge around the diastema. The two dorsal‐ and ventral‐most rays (peripheral principal rays, PPRs) arise independently and earlier than adjacent CPRs. Muscle and tendon markers reveal that different muscles attach to CPR and PPR sets. Conclusions: We propose that caudal fin symmetry originates from a central organizer that establishes the hypural diastema and bidirectionally patterns surrounding tissue into two plates of connective tissue and two mirrored sets of CPRs. Further, two peripheral organizers unidirectionally specify PPRs, forming a symmetric "composite" fin derived from three fields. Distinct CPR and PPR ontogenies may represent developmental modules conferring ray identities, muscle connections, and biomechanical properties. Our model contextualizes mechanistic studies of teleost fin morphological variation. Key Findings: Zebrafish pax2a null mutants display a defect in optic fissure closure and coloboma Loss of pax2b does not affect optic fissure development An endothelial‐specific subset of periocular mesenchyme cells fails to initially localize to the optic fissure in pax2a mutants At a later stage of optic fissure development both neural crest and endothelial‐derived periocular mesenchyme ectopically accumulate within the optic fissure Pax2a mutants have increased apoptosis in surrounding tissues, but not within the optic fissure margin cells, and apoptosis in part underlies the coloboma phenotype